2019
DOI: 10.1111/1365-2745.13151
|View full text |Cite
|
Sign up to set email alerts
|

Species asynchrony and response diversity determine multifunctional stability of natural grasslands

Abstract: A growing body of empirical evidence has suggested that biodiversity affects the simultaneous performance of multiple ecosystem functions (i.e. ecosystem multifunctionality). Given increasing environmental variability and uncertainty under global change, an emerging question is how biodiversity influences the stability of multiple functions (i.e. multifunctional stability). We currently know little, however, about the determinants and mechanisms of multifunctional stability, which is of practical importance fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
108
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(118 citation statements)
references
References 103 publications
(210 reference statements)
10
108
0
Order By: Relevance
“…Moreover, we found that the presence of an alternative host diminishes differences in average host survival and parasitism rates across different biotic and abiotic factors. Like in other studies, temporal complementarity between species (e.g., variation in growth rates), and a diversity of responses to environmental changes were major stabilizing mechanisms in our system (Zhang et al2013;Craven et al 2018;Sasaki et al 2019), though this is the first example using a host-parasitoid system. While most studies recognize that functional redundancy and trait diversity at any given time can positively affect community resilience to environmental changes, it is rarely considered that these community parameters continuously change during the development of individuals within the community.…”
Section: Effects Of Phenological Shifts On Outcomes Of Host-parasitoid Interactionssupporting
confidence: 57%
“…Moreover, we found that the presence of an alternative host diminishes differences in average host survival and parasitism rates across different biotic and abiotic factors. Like in other studies, temporal complementarity between species (e.g., variation in growth rates), and a diversity of responses to environmental changes were major stabilizing mechanisms in our system (Zhang et al2013;Craven et al 2018;Sasaki et al 2019), though this is the first example using a host-parasitoid system. While most studies recognize that functional redundancy and trait diversity at any given time can positively affect community resilience to environmental changes, it is rarely considered that these community parameters continuously change during the development of individuals within the community.…”
Section: Effects Of Phenological Shifts On Outcomes Of Host-parasitoid Interactionssupporting
confidence: 57%
“…An important outcome of our analysis is that asynchrony of species fluctuations is a key driver of community biomass stability at the small spatial scale in mediterranean and semi‐arid annual plant communities. This stability–asynchrony relationship predicted by theory (de Mazancourt et al, 2013), has been found in a wide range of ecosystems (Blüthgen et al, 2016; Valencia et al, 2020), particularly in perennial grasslands (Isbell et al, 2009, 2015; Sasaki & Lauenroth, 2011; Yang et al, 2012; Xu et al, 2015; Zhang et al, 2016; Lepš et al, 2018; Sasaki et al, 2019). Yet, this relationship has been scarcely examined in annual plant communities, particularly in low productivity regions.…”
Section: Discussionmentioning
confidence: 68%
“…Synergies typically occur when ecosystems are managed for resilience, because mechanisms that underpin ecological resilience (e.g. functional redundancy, functional complementarity, role of keystone species, vegetation structural heterogeneity) also contribute to the provision of multiple services [4,[48][49][50][51].…”
Section: Results (A) Traditional and Multi-functional Managementmentioning
confidence: 99%